Channels of sovereign risk spillovers and investment in the manufacturing sector - Sebastian M. Deininger; Dietmar G. Maringer (University of Basel, Center of Business and Economics (WWZ), 2017)
This paper identifies endogenous and exogenous indicators of firms' investment activity, and examine, in particular, the effect that these variables have in co-determining firms' investment decisions. Two channels of spillovers from sovereign risk to firms' capital expenditures are defined. The first channel, the "direct channel", describes responses in capital expenditures from an innovation in sovereign risk. The second channel, the "indirect channel", is a transmission mechanism in which spillovers from changes in sovereign risk indirectly affect a firm's capital expenditures via its capital market risk and profitability. While we observe that the direct risk channel is of major importance in Emerging and Developing Economies, it is comparatively small in Advanced Economies. In the case of the latter, contagion from changes in sovereign risk on firms' capital market risk plays a much more important role.
Keywords: C63; D81; E22; G31; 330; Capital expenditures; Risk spillovers; Panel VARX; Differential Evolution